Nigeria : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper; National Economic Empowerment and Development Strategy (NEEDS). (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents a Joint Staff Advisory Note on Nigeria's Poverty Reduction Strategy Paper. Within the framework of Nigeria's federation, policy coordination between the three tiers of government is critical for achieving poverty reduction objectives. The National Economic Empowerment and Development Strategy (NEEDS) provides for a considerable increase in public investments, which primarily reflects the government's desire to address the country's vast development requirements. NEEDS places considerable emphasis on strengthening public expenditure management to ensure that spending is effective, efficient, and clearly linked to the achievement of objectives of NEEDS.